Efficient synthesis of 2,3-aziridino-gamma-lactones from azetidin-2-ones - Kale, Ajaykumar S.; Deshmukh, A. R. A. S. (Synlett, 2005)
An efficient synthesis of enantiopure 2,3-aziridino-gamma-lactones from azetidin-2-ones is described. Acid-catalyzed tandem intramolecular azetidinone ring opening followed by aziridine ring formation via elimination of a mesylate group is the key step in this synthesis. 2,3-Aziridino-gamma-lactones are important precursors for biologically important glutamic acid derivatives.
Keywords: azetidin-2-ones; aziridines; glutamic acid; lactones

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Synthetic view of an analogue of the spiro-beta-lactone-gamma-lactam ring in oxazolomycins and lajollamycin - Mondal, Dhananjoy; Bera, Smritilekha (Synthesis-Stuttgart, 2010)
Herein, we describe a new synthetic strategy towards an analogue of the spiro-beta-lactone-gamma-lactam ring found in a class of potent antibiotics, the oxazolomycins and lajollamycin. The synthetic idea relies on the construction of two rings (beta-lactone and pyrrolidinone). The formation of the spiro-beta-lactone was accomplished by a crossed Cannizzaro reaction, while the 3,4-disubstituted pyrrolidinone ring was constructed by a titanium(IV) chloride mediated chelation-controlled double stereodifferentiating Crimmins aldol reaction of Garner's aldehyde.
Keywords: Crimmins aldol reaction; crossed Cannizzaro reaction; Garner's aldehyde; lactones; Mitsunobu reaction; pyrrolidine

Total synthesis of umuravumbolide and hyptolide through silicon-tethered ring-closing metathesis - Chowdhury, Partha Sarathi; Kumar, Pradeep (European Journal of Organic Chemistry, 2013)
The total synthesis of umuravumbolide and hyptolide has been achieved in a efficient manner by using temporary silicon-tethered ring-closing metathesis and cross-coupling reactions as key steps. The stereogenic centres were generated by means of proline-catalysed -aminoxylation of aldehydes and Brown's asymmetric allylation method.
Keywords: lactones; Metathesis; Silanes; synthetic methods; Total synthesis; Wittig reactions

Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones

Synthesis of alpha,beta-unsaturated delta-lactones by vinyl acetate mediated asymmetric cross-aldol reaction of acetaldehyde: mechanistic insights - Kumar, Manjeet; Kumar, Arvind; Rizvi, Masood; Mane, Manoj; Vanka, Kumar; Taneja, Subhash C.; Shah, Bhahwal Ali (European Journal of Organic Chemistry, 2014)
A tandem asymmetric cross-aldol reaction involving the in situ generation of acetaldehyde from vinyl acetate has been developed that may resolve the challenges associated with the handling of acetaldehyde. The simple protocol, mild reaction conditions and unique harmony of an organocatalyst with a biocatalyst make this method a valuable tool for the synthesis of asymmetric beta-hydroxy aldehydes. By using this methodology we have accessed alpha,beta-unstaurated delta-lactones as well as isochromenones with high enantioselectivities from both asymmetric beta-hydroxy aldehydes and ketones. Systemic density functional theory (DFT) studies were also performed to gain mechanistic insights into the role of hydrogen bonding in the asymmetric cross-aldol reaction of acetaldehyde and in the key cis/trans isomerisation step in the synthesis of d-lactones.
Keywords: Aldol reactions; asymmetric catalysis; lactones; reaction mechanisms

Synthesis of yangjinhualine A - Deore, Prashant S.; Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2015)
Selective reduction of 3-(4-hydroxyphenyl)-2-methylmaleic anhydride provides access the corresponding gamma-hydroxybutenolide natural product yangjinhualine A.
Keywords: anhydrides; lactones; Natural products; reduction; Regioselectivity

Total and semi-syntheses of antimicrobial thuggacin derivatives - Franke, Jana; Bock, Martin; Dehn, Richard; Fohrer, Joerg; Mhaske, Santosh B.; Migliorini, Antonella; Kanakis, Argyrios A.; Jansen, Rolf; Herrmann, Jennifer; Mueller, Rolf; Kirschning, Andreas (Chemistry-A European Journal, 2015)
The total and semi-synthesis of 13 new macrolactones derived from thuggacin, which is a secondary metabolite from the myxobacterium Sorangium cellulosum, are reported. The thuggacins have attracted much attention due to their strong antibacterial activity, particularly towards Mycobacterium tuberculosis. This study focuses on 1) thuggacin derivatives that cannot equilibrate by transacylation between the three natural thuggacins A-C, 2) the roles of the thiazole ring, and 3) the hexyl side chain at C2. Semi-synthetic O-methylation at C17 suppressed the transacylations without a substantial loss of antibacterial activity. Exchanging the C17-C25 side chain for simplified hydrophobic chains led to complete loss of antibacterial activity. Exchange of the thiazole by an oxazole ring or removal of the hexyl side chain at C2 had no substantial effect on the biological properties.
Keywords: antibiotics; lactones; Natural products; synthesis design; Total synthesis

First total synthesis of the proposed structure of pandangolide 1 - Show, Krishanu; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2018)
The first total synthesis of the proposed structure of pandangolide 1 is reported. The synthesis was carried out using both an organocatalytic approach and a chiral-pool approach. The required stereochemistry at C-3 and C-5 was installed by using an organocatalytic aldol reaction and a stereoselective ketone reduction. The construction of the 12-membered core was achieved by 2-methyl-6-nitrobenzoic anhydride-mediated Shiina lactonization. The structure of target molecule was confirmed unambiguously by single-crystal X-ray analysis, but the optical rotation and NMR spectroscopic data of the synthetic pandangolide 1 were found to be inconsistent with the natural product.
Keywords: lactones; Macrocycles; Natural products; structure elucidation; synthesis design; Total synthesis